Efficiency Effects on Iranian Banks’Performance and Stability during COVID-19 - Zahra Mojdeh; Zabihollah Taheri (Universitas Hayam Wuruk Perbanas, 2025)
This research investigates the impact of market concentration and operational efficiency on the financial performance (Return on Assets and Return on Equity) and financial stability (Z-score) of banks listed on the Tehran Stock Exchange, particularly during the unprecedented COVID-19 pandemicperiod. Utilizing panel data from 10 Iranian banks over the period 2014-2023, three distinct regression models were analyzed with the aforementioned dependent variables and interaction terms with a COVID-19 period dummy variable.Descriptive statistics and inferential tests, including the F-Limer and Hausman tests, were employed to identify the appropriate estimation models. Findings consistently indicate that operational efficiency significantly enhances bank performance and financial stability across all models, both during normal periods and during the pandemic. In contrast, market concentration does not demonstrate a statistically significant effect on performance or stability. DuringtheCOVID-19pandemic, the moderating effect of efficiency remains positive and significant, while concentration continues to show no impact.The models yield substantial explanatory power, with adjusted R-squared values ranging from 43% to 62%, and their F-statistics confirm overall robustness and significance. Durbin-Watson statistics suggest no first-order autocorrelation. These findings underscore the critical role of efficiency in sustaining bank profitability and resilience during economic shocks, providing relevant insights for policymakers and regulators aiming to enhance the banking sector’s preparedness for future crises